Effect of different levels of phosphorus on growth and yield of Cowpea varieties in Dang, Nepal - Aryal, Anjeela; Devkota, Ashbin Kumar; Aryal, Krishna; Mahato, Mohan (Journal of Agriculture and Natural Resources, 2021)
Variety having proper response to phosphorus for proper nutrient uptake and the optimum level of phosphorus for higher yield may be a way of increasing production and productivity in the context of Nepal. This experiment was carried out in Lamahi Municpality, Dang district of the Province no: 5, inner terai region of Nepal during the rainy season, 2019. The objective of the experiment was to study the effect of different phosphorus level on growth and development of different varieties of cowpea. The experiment was laid out in two factorial RCBD with two varieties (Aakash and Prakash) and five phosphorus level (0 kg ha-1, 20 kg ha-1, 40 kg ha-1, 60 kg ha-1 and 80 kg ha-1). The result revealed that variety Aakash showed the significantly higher yield of fresh pod (15.99 t ha-1) and yield attributing parameters like number of leaves at 45 DAS (35.22), leaf area at 45 DAS (70.23 cm²), pod diameter (0.77 cm), total number of fresh pods per plant (44.85) than Prakash variety (yield; 12.25 t ha-1). The parameters like number of branches and pod length were not affected by the variety used. In addition, the different level of P also affects the yield of the fresh pod of different varieties. The P level 40 kg ha-1 reported highest yield of fresh pod (20.18 t ha-1 and showed significantly higher number of leaves (38.9), number of branches (23.48), plant height (88.78cm), leaf area (81.89 cm²), pod length (17.76 cm), pod diameter (0.79 cm) and total number of fresh pods per plant (55.19) whereas control produced the lowest total yield of fresh pod (8.33 t ha-1), control (30.99) and 80 kg P ha-1 (30.86) produced the least number of leaves, control produced the least number of branches (17.31), control (63.77 cm) and 80 kg P ha-1 (67.83) produced the shortest plant, 80 kg P ha-1 produced the minimum leaf area (51.09 cm2), control produced least pod length (14.3 cm), pod diameter (0.74cm), total number of fresh pods (34.29). Similarly, interaction of Aakash and phosphorus dose 40 kg ha-1 produced significantly maximum number of leaves (43.07) and total yield of fresh pods (23.33 t ha-1). The results of the experiment revealed that variety Aakash with the phosphorus level 40 kg ha-1 seems the more profitable in Terai and inner Terai condition of Nepal. However, the results need to be confirmed for other varieties used by farmers in the region.